Could anyone please give me a hint on how to compute the following integral?

$$\int \sqrt{\frac{x-2}{x^7}} \, \mathrm d x$$

I'm not required to use hyperbolic/ inverse trigonometric functions.

  • $\begingroup$ There exists and elementary antiderivative, if helpful. $\endgroup$ – Brian Apr 1 '19 at 17:24
  • 1
    $\begingroup$ Are you required to not use them? $\endgroup$ – eyeballfrog Apr 1 '19 at 17:56
  • $\begingroup$ Yeah, unfortunately. @Brian yeah but i need to see the steps. $\endgroup$ – Just_Cause Apr 1 '19 at 18:04

Write your integrand in the form $$\frac{\sqrt{x-2}}{x^{7/2}}$$ and then substitute $$u=\sqrt{x}$$ so you will get $$2\int\frac{\sqrt{u^2-2}}{u^6}du$$ after this substitute $$u=\sqrt{2}\sec(s)$$ to get $$2\sqrt{2}\int\frac{\sin^2(s)\cos^2(s)}{4\sqrt{2}}ds$$

  • $\begingroup$ You made sqrt(x) a function of s? Could you elaborate more please? $\endgroup$ – Just_Cause Apr 1 '19 at 18:06

Write $y(x):=\sqrt{\frac {x-2} {x^7}}$.

Note that $$y'(x)= \frac {7-3x}{x^8} \frac 1 y $$

Hence $$\frac d {dx} x^n y=n x^{n-1} y + x^{n-8} \frac {7-3x} y.$$

Do the ansatz $$F(x)=\sum_{n=0}^k a_nx^ny ~~~~\text{ and } ~~~~F'(x)=y(x). $$

We get $$y\sum_{n=1}^{k}a_n nx^{n-1} +\frac 1 y\sum_{n=0}^{k} a_n x^{n-8} ({7-3x})=y $$

Thus $$\sum_{n=0}^{k} a_n x^{n-8} ({7-3x})=y^2(1-\sum_{n=1}^{k}a_n nx^{n-1}).$$

Now insert $y^2$ and get $$({7-3x})\sum_{n=0}^{k} a_n x^{n-1} = (x-2 )(1-\sum_{n=1}^{k}a_n nx^{n-1}) $$ or equivalently $$2-x+({7-3x})\sum_{n=0}^{k} a_n x^{n-1}+ (x-2)\sum_{n=1}^{k}a_n nx^{n-1}=0. $$

We solve this recursively.

The lowest order is $x^{-1}$. There we have $7a_0 x^{-1}=0$, so $a_0=0$.

In constant order: $2+7a_1-3a_0-2a_1=0$, so $a_1=-\frac 2 5$

In order $x$: $(-1+7a_2 -3 a_1 +a_1-4 a_2)x=0$ , so $a_2= \frac 1 3 (1+2 a_1)=\frac 1 {15}$

in order $x^2$: $(7a_3-3a_2+2a_2-6 a_3)x^2=0$, so $a_3=a_2=\frac 1 {15}$.

in order $x^3$: $(7a_4-3a_3+3a_3 - 8a_4)x^4=0$, so $a_4=0$

in order $x^n$ for $n>3$: $(7a_{n+1} - 3 a_n +n a_n - 2(n+1) a_{n+1})x^n$, so $a_{n+1}=\frac {n-3}{7-2(n+1)} a_n=0$.

In conclusion it follows that $$\int y(x)= const + F(x)= const+ \frac 1 {15} (-6x+ x^2+x^3) y $$


With $y:=\dfrac1x$,

$$\int\sqrt{\frac{x-2}{x^7}}dx=-\int\sqrt{\left(\frac1y-2\right)y^7}\,\frac{dy}{y^2}=-\int y\sqrt{1-2y}\,dy.$$

Then by parts,

$$-\int y\sqrt{1-2y}\,dy=\frac13y(1-2y)^{3/2}-\frac13\int(1-2y)^{3/2}dy=\frac13y(1-2y)^{3/2}+\frac1{15}(1-2y)^{5/2}$$


  • $\begingroup$ How could you get the y^6 out of the sqrt without facing issues with absolute value? $\endgroup$ – Just_Cause Apr 2 '19 at 16:58
  • $\begingroup$ @Just_Cause: I didn't worry about the domain of validity of the development. This must be added, with a thorough discussion, as a "post processing". $\endgroup$ – Yves Daoust Apr 2 '19 at 17:53
  • $\begingroup$ Yeah, I'll have this topic discussed ASAP. $\endgroup$ – Just_Cause Apr 3 '19 at 16:33
  • $\begingroup$ @YvesDaoust Oh, I think what he means is that you should have $\sqrt {x^6}=\sqrt {(x^3)^2}=|x^3|=|x||x^2|=x^2|x|=x^3$ only for $x\ge 0.$ Thus, your substitution in actual fact yields $\int{|y|\sqrt{1-2y}}\mathrm{d}y.$ This is what you should have computed. You only did the case when $|y|=y.$ The other case yields an improper integral since then $y$ becomes unbounded as $x\to0^-.$ Thus, it has to be dealt with specially. $\endgroup$ – Allawonder May 1 '19 at 18:27

Try the substitution $$ u=\frac{x-2}{x} $$

or equivalently

$$ x=\frac{2}{1-u} $$

  • $\begingroup$ Tried before, I'd face problems with absolute values cuz I get an even power under the sqrt $\endgroup$ – Just_Cause Apr 1 '19 at 18:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.